The bone house - Freeman, Brian, 1963- (Freeman, Brian, 1963- Cab Bolton novels., 2011)
When 16-year-old Glory, Tresa Fischer's wild-child younger sister, turns up dead on a beach near Mark and Hilary's Florida hotel, Mark becomes the number one murder suspect. Det. Cab Bolton, who isn't one to jump to conclusions, travels from Florida to Wisconsin to unravel Mark--and Glory's--complicated lives.